The al?theia of Cats. Balthus, Rilke and the problem of the “Open” - Molina Barea, María del Carmen (2022)
Maria Rilke and Balthazar Klossowski –Balthus–, which took the form of a book entitled Mitsou. Story of a Cat, illustrated by the young painter and foreworded by the poet. This case study serves as a guiding thread running through a deep analysis of the problem of the “Open”, a noumenic concept coined by Rilke in his creative exchange with Balthus. This concept was specifically discussed by Martin Heidegger. Thus, the present paper attempts to address the implications of affinity and confrontation between Rilke and Heidegger and to explore the metaphorical figure of the cat as the expression of certain animality within the unveiling that takes place in the Da-sein. For this purpose, it will also be necessary to explore theoretical key approaches taken from Ortega y Gasset and Schopenhauer, as well as critical positions particularly relevant in this field defended by Giorgio Agamben and Jacques Derrida, which tend towards an animalistic ontology of al?theia.